Analysis of Child Protection Efforts in Surabaya City thru the Family Learning Center (PUSPAGA) Program Co-Implementation Approach - Vidya Imanuari Pertiwi; Mohammad Rexy Prayitno (International Journal of Social, Economic, and Business, 2025)
To prevent violence against children in Indonesia, policy-based strategies must actively involve the community. This study examines how the Family Learning Center Program (PUSPAGA) in Surabaya is implemented using a co-implementation approach, as stated by Denita Cepiku (2021). Institutional arrangements, planning, communication strategies, public actor management, professional management, leadership, and accountability and performance management are the main topics of this research. The research method is a descriptive qualitative approach involving observation, in-depth interviews, and review of policy documents. Research shows that PUSPAGA Surabaya is able to integrate the government, workforce, and community in child protection efforts. However, the organization still faces problems such as a shortage of human resources and a lack of funds. This study shows that collaborative implementation methods can improve the sustainability of child protection programs if they are managed collaboratively, participatory, and focused on local needs.